A Critique Of Ecotourism Concepts In Tourism: An Analysis Of Mistakes And Misconceptions - Anggara, Bagas; Hardyanti , Hardyanti (Universitas Muhammadiyah Jember, 2024)
This study aims to critically evaluate ecotourism concepts by examining the gap between theoretical principles and their practical implementation. It seeks to uncover deviations and misconceptions in ecotourism practices that hinder the achievement of its intended goals. A qualitative approach is employed, utilizing an extensive literature review to identify and analyze the shortcomings in the application of ecotourism principles. This method allows for a comprehensive assessment of existing practices and the underlying causes of their failures. The research reveals significant deficiencies in the implementation of ecotourism, including inadequate environmental conservation, insufficient community involvement, and a lack of educational initiatives. These issues contribute to environmental degradation and socio-cultural conflicts, demonstrating a clear disconnect between the ideals of ecotourism and its actual practice.This study offers original insights into the persistent challenges facing ecotourism by highlighting the importance of adhering strictly to its principles. The research provides practical recommendations for improving ecotourism practices, focusing on enhanced community engagement, effective conservation, and sustainable management, thereby contributing to the broader discourse on sustainable tourism.